ANALYSIS OF DAILY TEST QUESTIONS ON THE VIRUS MATERIAL CLASS X SMAN 5 SOLOK SELATAN - Liza Yulia Sari (Jurnal Pelita Pendidikan, 2020)
Based on the results of interviews with two biology teachers at SMAN 5 Solok Selatan on Virus material from daily tests of class X students in semester 1 of the 2017/2018 academic year are still below the Minimum Mastery Criteria (KKM) set by schools is 75. The low learning outcomes of students are wrong one is caused by the evaluation tools used which may be too difficult. This study aims to provide information about the validity, reliability, difficulty index, distinguishing features of the test questions on the material of class X Virus SMAN 5 Solok Selatan in the academic year 2018/2019. This type of research is descriptive research. Based on the results of the analysis of the validity of the questions on daily test questions on the material of class X virus SMAN Negeri 5 South Solok, the average validity of questions is 0.96 including high validity criteria, reliability analysis results of daily test questions that are 1.00 which includes very high reliability criteria, index analysis the difficulty of 46 questions is that 38 questions (82.60%) are sufficient, and 8 questions (17.39%) are too easy, so the daily test questions are of moderate criteria. Distinguishing power analysis obtained enough criteria as many as 33 questions (71.73%), good criteria 7 questions (15.21%), bad criteria 5 questions (10.86%), very bad criteria of 1 question (2.17%) . The conclusion of this study is a matter of daily tests on the material of Class X Virus SMAN 5 Solok Selatan in the 2018/2019 academic year in terms of validity, reliability, difficulty index and distinguishing features have met the criteria of good questions.